Jahresbericht des Vereins Kunsthalle Bern 1978 / 1979. - Gachnang, Johannes; Kunsthalle Bern (Bern : Kunsthalle Bern, 1979)
Toroni, Niele ; Byars, James Lee ; Brecht, George ; Kiefer, Anselm ; etc.
Duits
boek